MODERN STATE AND PROGNOSES OF DEVELOPMENT OF WORLD MARKET OF NANOPOWDERS - Malyshev , Victor; Shakhnin , Dmitry; Zinchenko , Vasiliy; Vodennikova , Oksana; Sergienko , Tatiana; Vodennikova , Larisa (Scientific Journal "Metallurgy", 2020)
The analysis of quality of heating is executed for heat treatment of steel blanks at existent technology of heating of two-cell thermal furnaces mixture natural and domain gases. There is offered rational technology of their heating with combining of the mentioned fuel constituents, realization of which will allow to increase the volume expense of products of combustion during all cycle of heat treatment, and, consequently, to reduce the unevenness of heating of steel blanks. The wide turn-down of thermal power of furnaces during realization of the multi-stage temperature-sentinel modes of heat treatment of metal predetermines requirements to incineration of gaseous fuel for her different periods. During experimental researches studied distribution of temperature on length of working chamber, and also warming under heat treatment of purveyances from steel by the 4Х5МФ1С section of 370 х a 370 mm and by general mass 26,7 т. Distribution of temperature in steel purveyances was controlled by the use flexible hromel- alumel thermels, set on the surface of metal charge on long purveyances; control of temperature in the swept volume of furnace was executed by the stationary set temperature-sensitive element. The results of the executed researches allowed to draw conclusion about the necessity of stabilizing of the gas-dynamic mode of thermal furnace by the increase of by volume expense of foods of burning through the change of technology of her heating. The task of translation of furnaces of this type on heating with separate admission natural and domain gases, and also their subsequent combining immediately in front of gas-rings are examined. At that rate a management thermal power of thermal furnace is carried out by the simultaneous operating both on the regulators of expense of separate components of fuel for providing of the set temperature in her swept volume and on the regulator of volume of foods of burning in periods of self-control and cooling of metal. On a thermal furnace it is set the results of subsequent experiments, that during translation of her on separate admission natural and domain gases the overfall of temperature in the horizontal section of the swept volume of furnace goes down to 15-20 C, and after length gardens of steel purveyances - to 25-30 С. The complex of experimentally-calculation researches of thermal work of two-cell thermal heater is executed during translation of her on a separate serve natural and domain gases, and also surplus air. Advantages of the offered method of heating of furnace of this type are shown.